Synthesis of the Tetrasaccharide Repeating Unit Corresponding to the O-Antigen of Providencia alcalifaciens O7:H7 Strain - Rana, Abhijit; Misra, Anup Kumar (Synthesis, 2025)
Synthesis of the tetrasaccharide corresponding to the O-antigen of Providencia alcalifaciens O7:H7 strain was achieved in satisfactory yield by applying a stereoselective glycosylation strategy. Stereoselective incorporation of β-l-rhamnose, α-d-glucosamine and α-d-glucose moieties in the tetrasaccharide was achieved in very good yield. The d-glucuronic acid moiety in the tetrasaccharide was achieved by late-stage TEMPO–bis(acetoxy)iodobenzene (BAIB)-mediated regioselective oxidation of the primary hydroxyl group of the d-glucose moiety. Thioglycosides were used as glycosyl donors in the presence of a combination of N-iodosuccinimide (NIS) and triflic acid (TfOH) as thiophilic promoter.
Keywords: carbohydrates; glycosylation; glycosides; oligosaccharides; oxidation; synthesis